2016
DOI: 10.1038/srep23669
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Liver Epithelial Cell-derived Ig Expression in μ chain-deficient mice

Abstract: Growing evidence indicates that B cells are not the only source of immunoglobulin (Ig). To investigate this discovery further, we used μMT mice, which have a disruption of the first transmembrane exon of the μ heavy chain and do not express the membrane form of IgM. These mice lack mature B cells and thus serve as a good model to explore Ig expression by liver epithelial cells. We found that Ig heavy chains (μ, δ, γ and α) and light chains (κ and λ) were expressed in sorted liver epithelial cells of μMT mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Positive staining of Igγ, γ4, κ and λ chains was detected in the cytoplasm of podocytes, thus indicating that podocytes may express IgG. Shao et al ( 35 ) reported that IgM was expressed and presented in kidney tubules in µ MT mice, which have hardly any IgM in circulation due to the disruption of the µ heavy chain, thus lacking mature B cells. Compared with commercial antibodies, the RP215 antibody recognizes a specific carbohydrate-associated epitope on non-B cell-derived Igγ ( 34 ); in the present study, RP215 mAb detected IgG more clearly both on the cell membranes and in the cytoplasm, suggesting that podocyte-derived IgG was more likely to be non-B cell derived as the findings of Liao et al ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive staining of Igγ, γ4, κ and λ chains was detected in the cytoplasm of podocytes, thus indicating that podocytes may express IgG. Shao et al ( 35 ) reported that IgM was expressed and presented in kidney tubules in µ MT mice, which have hardly any IgM in circulation due to the disruption of the µ heavy chain, thus lacking mature B cells. Compared with commercial antibodies, the RP215 antibody recognizes a specific carbohydrate-associated epitope on non-B cell-derived Igγ ( 34 ); in the present study, RP215 mAb detected IgG more clearly both on the cell membranes and in the cytoplasm, suggesting that podocyte-derived IgG was more likely to be non-B cell derived as the findings of Liao et al ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Ig synthesis has largely been considered an aberrant feature of transformed somatic cells. However, recent studies in neuronal cells [ 46 ], epithelial cells [ 47 ], epidermal cells [ 48 ] and endothelial cells [ 49 ] suggest that non-transformed cell types are also capable of “ectopic” immunoglobulin production.…”
Section: Discussionmentioning
confidence: 99%
“…Our single cell sequencing results showed that, unlike B cell-derived Igk, which shows diversity, cardiomyocyte-derived Igk exhibited a very conservative VkJk usage and pattern and tended to express IgkV17-121 (28.3%, 95/336), IgkV9-120 (25%, 84/336), and IgkV14-100 (15.5%, 52/336) in cardiomyocytes in adult mice. It is worth noting that the conservative characteristics of cardiomyocyte-derived Igk were similar to those of Igk in hepatocytes and other non-B cells, especially IgkV9-120, which has been found to be highly frequently expressed in other non-B cell lineages 34,35 . However, the expression frequency of the above VkJk usages in B cells was less than 3%.…”
Section: Discussionmentioning
confidence: 73%
“…For several decades, B cells and differentiated plasma cells were thought to be the only sources of Igs. However, in recent years, many studies from our group and others have revealed that Igs are not only produced by B cells but also expressed by non-B cell lineages, including epithelial cells, neurons and germ cells of the testis [1][2][3][4][5][6][7][8] . In addition to serving as natural antibodies for immune defense, non-B Igs also exhibit diverse biological functions; for example, renal podocyte-derived IgG promotes cell adhesion and survival 9,10 .…”
Section: Introductionmentioning
confidence: 99%